"The Heartbeat of Hamilton": Researcher's Reflections on Hamilton Children's Engagement With Visual Research Methodologies to Study the Environment. Issue 4 (20th November 2015) - Moola, Fiona; Johnson, Jay; Lay, Jennifer; Krygsman, Seychelle; Faulkner, Guy
Traditionally, children's "voices" have been underrepresented in the field of cultural geography. Rather, "adultist views" dominate. In this article, we describe the methodological process of undertaking a comprehensive, participatory action visual methodologies project known as the Hamilton Photovoice Project (HPP) with children from low socioeconomic status neighborhoods in Hamilton, Ontario, Canada. We also discuss the lessons that we have learned along the way. The purpose of the HPP was to investigate how children in downtown Hamilton experience their metropolitan landscape. Specifically, we examined walking routes for the purposes of identifying desired environmental changes that may increase the use and enjoyment of community walking routes and spaces along routes. In doing so, we discuss what was learned from the methodological process of collecting and working with children's visual productions, including how children appear to use visual methods. Although children's visual productions appear to convey complex emotional, social, and political sentiments about their spatial experiences and desired environmental changes, the methodological process is invariably constrained by the institutions that govern and police children today during the research process. Thus, this study contributes toward the ongoing dialogue about the merits and tensions inherent to using children's visual productions as a way to capture perceptions toward place.